On the nexus of monetary policy and financial stability: Effectiveness of macroprudential tools in building resilience and mitigating financial imbalances - Evren Damar; Miguel Molico (Bank of Canada, 2016)
This paper reviews the Canadian and international evidence of the effectiveness of macroprudential policy measures in building resilience and mitigating financial imbalances. The analysis concludes that these measures have broadly achieved their goal of increasing the overall resilience of the financial system to the buildup of imbalances and increasing the financial system's ability to withstand adverse shocks. However, evidence of their effectiveness in providing countercyclical stabilization by curbing credit growth ("leaning against the financial cycle") is limited. Among the different types of macroprudential measures, those that are "sectoral" in nature and/or those that target borrowers are most effective in leaning against the financial cycle. Overall, the observed effectiveness of macroprudential tools in addressing systemic risk implies that these policies can be complementary to monetary policy in achieving the goals of macroeconomic and financial stability.
Keywords: E51; E58; G18; G28; 330; Financial stability; Financial system regulation and policies; Credit and credit aggregates